A study on determining resource dependence strategies for international new ventures - Çelik, Merve (My University, 2020)
This study analyzes how new ventures reduce their resource dependencies in international markets. The international entrepreneurship literature deals with the relationship between new ventures and resources. However, there is no consensus on strategies applied to reduce resource dependencies. Moreover, these strategies‘ affiliation with resources types were overlooked. Accordingly, the hole in the international entrepreneurship literature will be eliminated with this study. The fundamental contribution of this study will be that defining which strategies reduce which resource dependencies by detecting the strategies applied by international new ventures. In this study, eight international new ventures, located in Istanbul and operating in different sectors, were determined and they were analyzed by use of the qualitative research method. As parallel with the purpose and characteristics of the study, the multiple case study pattern was preferred. The findings revealed that partnership agreements of new ventures and activities of senior executive team members play a fundamental role in decrease in resource dependency. As the conclusion of the study, it was presented that interorganizational partnership agreements and activities of senior executive team members provide a decrease in dependencies on intangible and tangible resources, mainly intangible (i.e. network) ones.

Bu çalışma, yeni girişimlerin uluslararası pazarlarda kaynaklara olan bağımlılıklarını nasıl azalttıklarını incelemektedir. Uluslararası girişimcilik literatürü, yeni girişimlerin kaynaklarla olan ilişkileriyle ilgilenmektedir. Ancak, kaynak bağımlılığını azaltmak için uygulanan stratejiler ile ilgili ortak bir karar yoktur. Ayrıca stratejilerin kaynak çeşitleriyle ilişkilendirilmesi gözardı edilmiştir. Dolayısıyla, uluslararası girişimcilik literatüründeki bu açık giderilecektir. Bu çalışmanın temel katkısı, uluslararası yeni girişimlerin uyguladıkları kaynak bağımlılığı azaltma stratejilerini belirleyerek, bu stratejilerin hangi kaynaklara olan bağımlılıklarını azalttıklarını ortaya koymaktır. Araştırmada, İstanbul'da farklı sektörlerde bulunan sekiz uluslararası yeni girişim tespit edilmiş ve nitel araştırma yöntemi kullanılarak incelenmiştir. Araştırmanın amacına ve niteliğine uygun olarak çoklu vaka çalışması deseni tercih edilmiştir. Bulgular, yeni girişimlerin ortaklık anlaşmalarının ve üst yönetim ekibi faaliyetlerinin kaynak bağımlılığının azaltılmasında önemli bir rol oynadığını ortaya koymuştur. Araştırmanın sonucu olarak örgütler arasında yapılan ortaklık anlaşmaları ve üst yönetim ekibi faaliyetlerinin ağırlıklı olarak soyut kaynaklar (örn. network) olmak üzere soyut ve somut kaynaklara olan bağımlılıkların azaltılmasını sağladığı ortaya konulmuştur.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2020
Keywords: Uluslararası girişimcilik; Uluslararası yeni girişimler; Kaynak bağımlılığı; Örgütlerarası ilişkiler; Şebeke ilişkileri; International entrepreneurship; International new venture; Resource dependency; Interorganizational relationship; Network relations